VD_FINDINFO HC / 2011 / 319 vom 6. Juni 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, LOGEMENT DE LA FAMILLE, AVANCE DE FRAIS, CONJOINT | 125 al. 1 CC, 176 al. 1 ch. 1 CC, 176 al. 1 ch. 2 CC, 308 al. 1 let. b CPC (CH)